COCRWC ALLOY DESIGN FOR HARDFACING APPLICATIONS IN HEEAVY EQUIPMENT WITH STACKING FAULT ENERGY CALCULATION USING THERMODYNAMICS AND FIRST-PRINCIPLES METHODS - Helmi Khairi, Ardhia
CoCrWC alloy is a cobalt-based alloy which has another name, namely Stellite 6. This alloy was developed due to its good mechanical properties such as high strength, corrosion resistance and wear resistance making it very suitable for hardfacing applications on heavy equipment parts that are subjected to cyclic loading and susceptible to abrasive wear. This study focuses on increasing the value of stacking fault energy (SFE) of CoCrWC alloy to inhibit deformation-induced phase transformation (DIMT) and critical parameters that affect mechanical properties. This study provides new insights into the mechanical properties and improves wear resistance of CoCrWC alloys for heavy equipment hardfacing applications. Calculations and simulations were carried out to study the effect of temperature and concentration of the addition of alloying elements Fe, Ni, and Mn to the CoCrWC alloy. We use a thermodynamic method to predict the SFE value at a temperature of 0? to 300?. To increase the SFE value, we added alloying elements from previous studies that can increase the SFE value of an alloy, namely the elements Fe, Mn, and Ni. The effect of the concentration of the alloying elements on the SFE value was carried out by simulating through first-principles simulations at the concentrations of the alloying elements 4.2 and 8.4 at.%. Electronic structure analysis was also carried out to determine the effect of adding alloying elements on the charge accumulation area and total DOS (Density of States). Based on the results of thermodynamic calculations, the SFE value of the CoCrWC alloy is very low (-65 mJ/m2) which is in accordance with the SFE calculations from the literature (-57 mJ/m2). Fe, Ni, and Mn will increase the SFE value when added to certain compositions using both thermodynamic calculations and first-principles simulations. The addition of Fe will increase the most significant SFE value in thermodynamic calculations and the addition of Ni in the first-principles simulation. The Mn element will decrease the SFE value first and then will increase at a certain composition. The difference between the SFE values of thermodynamics and firstprinciples calculations is still quite high because it is difficult to model the atomic structure in first-principles which results in fluctuating SFE values depending on the position of the atoms. The addition of Fe, Ni, and Mn elements will shrink the area of charge accumulation and increase the DOS value, thereby increasing the SFE value. CoCrWC alloy design suggestion is the addition of Fe up to 22 wt.% so as to increase the value of SFE and inhibit the formation of SIMT and can increase fatigue life.